Effect of phosphate-solubilizing bacteria on phosphorus dynamics and the bacterial community during composting of sugarcane industry waste - Estrada-Bonilla, German A.; Lopes, Cintia M.; Durrer, Ademir; Alves, Paulo R.L.; Passaglia, Nicolle; Cardoso, Elke J.B.N. (Systematic and applied microbiology, 2017)
Sugarcane processing generates a large quantity of residues, such as filter cake and ashes, which are sometimes composted prior to their amendment in soil. However, important issues still have to be addressed on this subject, such as the description of bacterial succession that occurs throughout the composting process and the possibilities of using phosphate-solubilizing bacteria (PSB) during the process to improve phosphorus (P) availability in the compost end product. Consequently, this study evaluated the bacterial diversity and P dynamics during the composting process when inoculated with Pseudomonas aeruginosa PSBR12 and Bacillus sp. BACBR01. To characterize the bacterial community structure during composting, and to compare PSB-inoculated compost with non-inoculated compost, partial sequencing of the bacterial 16S rRNA gene and sequential P fractionation were used. The data indicated that members of the order Lactobacillales prevailed in the early stages of composting for up to 30 days, mostly due to initial changes in pH and the C/N ratio. This dominant bacterial group was then slowly replaced by Bacillales during a composting process of up to 60 days. In addition, inoculation of PSB reduced the levels of Ca-bound P by 21% and increased the labile organic P fraction. In PSB-inoculated compost, Ca-P compound solubilization occurred concomitantly with an increase of the genus Bacillus. The bacterial succession and the final community is described in compost from sugarcane residues and the possible use of these inoculants to improve P availability in the final compost is validated.